Psychological Distress Among High School Students in Bangkok Thailand - Chatchai Thanachoksawang; Sara Arphorn; Suchinda Jarupat Maruo; Suwatsa Punneng; Tomohiro Ishimaru; Goontalee Bangkadanara (Health Psychology Research)
# Introduction